2012
DOI: 10.1117/12.925586
|View full text |Cite
|
Sign up to set email alerts
|

Performance and on-sky optical characterization of the SPTpol instrument

Abstract: In January 2012, the 10m South Pole Telescope (SPT) was equipped with a polarization-sensitive camera, SPTpol, in order to measure the polarization anisotropy of the cosmic microwave background (CMB). Measurements of the polarization of the CMB at small angular scales (∼several arcminutes) can detect the gravitational lensing of the CMB by large scale structure and constrain the sum of the neutrino masses. At large angular scales (∼few degrees) CMB measurements can constrain the energy scale of Inflation. SPTp… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 13 publications
1
12
0
Order By: Relevance
“…The predicted noise levels agree to within the 10-20% systematic uncertainties of preliminary on-sky noise measurements. 38 projected map depths for SPTpol also agree with a simple scaling from SPT-SZ using its measured focal plane sensitivity and survey map depth, which already include all overheads, data cuts, and observing inefficiencies, and would similarly predict final SPTpol survey depths of ∼ 9 and ∼ 5µK-arcmin for the 90 and 150 GHz bands, respectively.…”
Section: Projections and Performancesupporting
confidence: 64%
See 2 more Smart Citations
“…The predicted noise levels agree to within the 10-20% systematic uncertainties of preliminary on-sky noise measurements. 38 projected map depths for SPTpol also agree with a simple scaling from SPT-SZ using its measured focal plane sensitivity and survey map depth, which already include all overheads, data cuts, and observing inefficiencies, and would similarly predict final SPTpol survey depths of ∼ 9 and ∼ 5µK-arcmin for the 90 and 150 GHz bands, respectively.…”
Section: Projections and Performancesupporting
confidence: 64%
“…39,40 This low-noise system introduces a small current-noise term that is sub-dominant to other noise sources under normal operating parameters. 38 For SPTpol we multiplex 12 resonant channels on each SQUID, 19 with frequency separation between channels of ∼ > 60 kHz to minimize crosstalk. A total of 144 SQUIDS are used to readout the 1536 optical TES channels in addition to various dark TES bolometers and other calibration channels.…”
Section: Readoutmentioning
confidence: 99%
See 1 more Smart Citation
“…This matches how many focal planes are designed, e.g. the Planck (Maffei et al 2010), SPTpol (George et al 2012) and ACTpol (Thornton et al 2016) receivers. The focal planes for SO will also be at least partly composed of such combinations of detector orientations (Galitzki et al 2018).…”
Section: Introductionmentioning
confidence: 62%
“…Indeed, our early devices were going unstable at operating bias points of ∼ 0.8 R N , near typical operating points for our 150 GHz detectors. 31 We tested several TES geometries to find an appropriate transition shape and deposited a non-superconducting metal, palladium gold ("bling"), around each TES to increase the detectors' time constants. We found that having a solid bar for the TES and extending the bling over the edge of the microstrip leads heading to the TES and into the TES region itself lowered α sufficiently while keeping 150 GHz detector loop gains in transition at an acceptable level.…”
Section: Dark Propertiesmentioning
confidence: 99%